2008
DOI: 10.1111/j.1460-9568.2008.06455.x
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol self‐administration acutely stimulates the hypothalamic‐pituitary‐adrenal axis, but alcohol dependence leads to a dampened neuroendocrine state

Abstract: Clinical studies link disruption of the neuroendocrine stress system with alcoholism, but remaining unknown is whether functional differences in the hypothalamic-pituitary-adrenal (HPA) axis precede alcohol abuse and dependence or result from chronic exposure to this drug. Using an operant self-administration animal model of alcohol dependence and serial blood sampling, we show that long-term exposure to alcohol causes significant impairment of HPA function in adult male Wistar rats. Acute alcohol (voluntary s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
225
2
6

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 263 publications
(254 citation statements)
references
References 85 publications
20
225
2
6
Order By: Relevance
“…Allostatic changes in brain reward and stress systems are thought to mediate many of these symptoms. We previously reported that dysregulation of the hypothalamic-pituitary-adrenal (HPA) axis, the principal neuroendocrine stress system, and consequent alterations in brain glucocorticoid receptor (GR) expression accompany compulsive-like alcohol intake in rats (5,6). Despite these strong preclinical findings and evidence for dysregulation of the HPA axis in alcoholism (7,8), a role for GR signaling in humans who suffer from alcohol dependence has yet to be determined.…”
Section: Introductionmentioning
confidence: 99%
“…Allostatic changes in brain reward and stress systems are thought to mediate many of these symptoms. We previously reported that dysregulation of the hypothalamic-pituitary-adrenal (HPA) axis, the principal neuroendocrine stress system, and consequent alterations in brain glucocorticoid receptor (GR) expression accompany compulsive-like alcohol intake in rats (5,6). Despite these strong preclinical findings and evidence for dysregulation of the HPA axis in alcoholism (7,8), a role for GR signaling in humans who suffer from alcohol dependence has yet to be determined.…”
Section: Introductionmentioning
confidence: 99%
“…33) Glucocorticoid hormones are the final step in the activation of the HPA axis and are known to function in the biological response to stress. 34) In alcohol dependence, the HPA axis is dysregulated in both humans 35) and rodents, 8,36,37) but the effects of this dysregulation are still unclear. Here, we speculated that regulation of the HPA axis, such as by changes in the blood corticosterone level, may play an important role in the impaired recognition after the discontinuation of ethanol treatment.…”
Section: )mentioning
confidence: 99%
“…7) Interestingly, the plasma concentration of corticosterone is increased by acute ethanol challenge, but this response is attenuated by chronic exposure. 8) It has been reported that corticosterone promotes learning and memory in non-stressed rodents, while the chronic administration of corticosterone has opposite effects. [9][10][11] Although there is increasing evidence that the stress hormone corticosterone may modulate learning and memory, the effects of chronic exposure to stress and acute administration of corticosterone on the impaired recognition after ethanol withdrawal are not sufficiently clear.…”
mentioning
confidence: 99%
“…Akut alkol alımının dolaşımdaki adrenokortikotropik hormon (ACTH) ve kortizolü artırdığı bilinmektedir (Zhou ve ark. 2000, Richardson ve ark. 2008, Willey ve ark.…”
Section: Crh Sistemiunclassified